Growth and yield of lettuce (Lactuca sativa L.) grown on different planting media volumes in a floating cultivation system - Fitra Gustiar; Duwi Septiani; Hilda Agustina; Fikri Adriansyah; Fitri Ramadhani (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2025)
Lettuce (Lactuca sativa L.) is one of the vegetables that is widely loved because of its taste and nutritional content. The increase in lettuce production can be increased by the use of swamp land with floating cultivation during the flood season. The size of the pots used in floating system cultivation will affect the growth and number of plants that will be produced. The study aimed to determine the optimal of planting media volume on the growth and yield of lettuce in floating cultivation system. The research used a randomized block design with 4 treatments of planting media volume, namely 1.9 L (P1), 2.7 L (P2), 3.6 L(P3), and 5 L (P4). Each treatment was repeated 4 times and each replication consisted of 5 plants. The results showed that at the beginning of the growth of the media volume of 2.7 L would be faster, but at the time of harvest almost all parameters showed that plants with a media volume of 5 L produced a larger plant weight than the plant unit. Although the use of smaller volumes of media results in a smaller plant weight, the raft is able to accommodate a larger number of pots. So that the use of a media volume of 1.9 L will be better used for floating lettuce production.